INTEGRATED PARTICIPATIVE INSTRUCTIONAL SUPERVISION PLANNING AT PUBLIC JUNIOR HIGH SCHOOLS: A MULTISITE CASE STUDY AT THREE MIDDLE SCHOOLS IN BLITAR, EAST JAVA - Supriyono , (Universitas Islam Balitar, 2018)
This research was aimed at revealing the integrated participative instructionalsupervision planning carried out at three public middle schools in Blitar, East Java. Thisstudy followed qualitative approach by using multisite case study design. This study washeld in three different public middle schools in Blitar, East Java. Data was collected byusing Observation, Interview, and Documentation. To ensure the data validity andreliability, assessments on credibility, dependability, conformability, and transferabilitywere employed. Subjects were chosen by purposive sampling with snow ballingtechnique involving district supervisors, principals, and senior teachers. Data wasanalyzed using interactive and modified induction methods. This research concluded thatThe integrated participative instructional supervision resulted the enhancement ofteachers ’ performance and students learning outcomes as well as to the attainment of thedepartment of education and culture and schools ’ visions and mission. It is suggested tobe further researched using research and development approach.